Prognostic factors and risk groups in T1G3 non-muscle-invasive bladder cancer patients initially treated with Bacillus Calmette-Guérin: results of a retrospective multicenter study of 2451 patients - Gontero, Paolo; Sylvester, Richard; Pisano, Francesca; Joniau, Steven; Vander Eeckt, Kathy; Serretta, Vincenzo; Larré, Stéphane; Di Stasi, Savino; Van Rhijn, Bas; Witjes, Alfred J; Grotenhuis, Anne J; Kiemeney, Lambertus A; et al. (European urology, 2015)
BACKGROUND: The impact of prognostic factors in T1G3 non-muscle-invasive bladder cancer (BCa) patients is critical for proper treatment decision making. OBJECTIVE: To assess prognostic factors in patients who received bacillus Calmette-Guérin (BCG) as initial intravesical treatment of T1G3 tumors and to identify a subgroup of high-risk patients who should be considered for more aggressive treatment. DESIGN, SETTING, AND PARTICIPANTS: Individual patient data were collected for 2451 T1G3 patients from 23 centers who received BCG between 1990 and 2011. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Using Cox multivariable regression, the prognostic importance of several clinical variables was assessed for time to recurrence, progression, BCa-specific survival, and overall survival (OS). RESULTS AND LIMITATIONS: With a median follow-up of 5.2 yr, 465 patients (19%) progressed, 509 (21%) underwent cystectomy, and 221 (9%) died because of BCa. In multivariable analyses, the most important prognostic factors for progression were age, tumor size, and concomitant carcinoma in situ (CIS); the most important prognostic factors for BCa-specific survival and OS were age and tumor size. Patients were divided into four risk groups for progression according to the number of adverse factors among age ≥ 70 yr, size ≥ 3 cm, and presence of CIS. Progression rates at 10 yr ranged from 17% to 52%. BCa-specific death rates at 10 yr were 32% in patients ≥ 70 yr with tumor size ≥ 3 cm and 13% otherwise. CONCLUSIONS: T1G3 patients ≥ 70 yr with tumors ≥ 3 cm and concomitant CIS should be treated more aggressively because of the high risk of progression. PATIENT SUMMARY: Although the majority of T1G3 patients can be safely treated with intravesical bacillus Calmette-Guérin, there is a subgroup of T1G3 patients with age ≥ 70 yr, tumor size ≥ 3 cm, and concomitant CIS who have a high risk of progression and thus require aggressive treatment.
Keywords: senioři; Disease Progression; BCG Vaccine; BCG; Retrospective Studies; nádory močového měchýře; progrese nemoci; Prognosis; Risk Assessment; Middle Aged; mužské pohlaví; Cystectomy; Neoplasm Recurrence, Local; míra přežití; lokální recidiva nádoru; Non–muscle-invasive bladder cancer; Follow-Up Studies; věkové faktory; následné studie; Prognostic factors; Carcinoma in Situ; ženské pohlaví; prognóza; hodnocení rizik; retrospektivní studie; Humans; Tumor Burden; tumor burden; Survival Rate; lidé středního věku; rizikové faktory; Age Factors; Urinary Bladder Neoplasms; adjuvancia imunologická; Bacillus Calmette-Guérin; Adjuvants, Immunologic; BCG vakcína; Female; Aged; karcinom in situ; Risk Factors; lidé; Male; cystektomie; T1G3